Bantuan Hukum dan Kebenaran (Veritas): Membongkar Norma yang Destruktif dan Menetapkan Rekonstruksi - Susilo, Erwin; Rafi, Muhammad (Jurnal Hukum IUS QUIA IUSTUM, 2026)
This research is based on the issue of limited access to legal assistance for suspects or defendants in the Indonesian criminal justice system. The provisions in Article 155 paragraphs (1) and (2) of the New Criminal Procedure Code remain stipulating a minimum criminal penalty and various administrative requirements for obtaining free legal assistance. These provisions pose the potential to hinder suspects or defendants, especially those who are incapacitated or detained, from obtaining effective legal assistance. Consequently, there is an imbalance in the position between the state and individuals in criminal justice, which can affect the search for material truth ( veritas ) as the main objective of criminal procedure law. This research aims to analyse the role of advocates in assisting to uncover veritas in criminal justice and formulate a more effective regulatory concept for legal assistance. The study uses a doctrinal legal research method with a conceptual approach and a statutory approach, which is analysed qualitatively against legal norms governing legal assistance. The results indicate that the presence of advocates plays an important role in balancing the relationship between the state and suspects or defendants and strengthening the fair evidentiary process. Therefore, this research recommends the reconstruction of legal assistance regulations by removing the minimum criminal penalty limit in Article 155 of the New Criminal Procedure Code and simplifying the administrative requirements for detained suspects or defendants. This reformulation is necessary to ensure that legal assistance truly functions as an instrument to guarantee equality before the law and support the search for material truth in criminal justice.